Troponin T release after heart transplantation. Issue 5 (May 1993) - Zimmermann, R; Baki, S; Dengler, T J; Ring, G H; Remppis, A; Lange, R; Hagl, S; Kübler, W; Katus, H A
Abstract : BACKGROUND--For the diagnosis of myocardial cell damage the measurement of the serum concentrations of myofibrillar antigens has several potential advantages over the assessment of traditional serological markers. These include the expression of myofibrillar antigens as cardiospecific isoforms and their high intracellular concentrations. Recently a sensitive and specific enzyme immunoassay for cardiac troponin T has been developed that shows little cross-reactivity with skeletal isoforms. OBJECTIVE--To characterise myocardial cell damage after orthotopic heart transplantation, concentration of circulating troponin T were measured prospectively in serial blood samples from 19 consecutive patients taken during the first three months after transplantation. RESULTS--Mean (SD) serum concentrations of cardiac troponin T reached a maximum of 3.6 (1.8) micrograms/l at 7.1 (4.2) days after transplantation and remained higher than 0.5 micrograms/l (twice the detection limit of the assay) in all patients for at least 43 days (mean (SD) 59 (20) days). There was considerable variation in cumulative troponin T release (area under the concentration curve) between the patients (ranging from 27 to 150 micrograms x days/l) that was not related to the total ischaemic time before transplantation or to the patient's renal or hepatic function, preoperative cardiac diseases, major histocompatibility complex matching or the number of complications related to rejection. CONCLUSIONS--Because the half life of cardiac troponin T serum is 2 h the current data show that antigen continued to be released from implanted hearts during the first postoperative months in quantities similar to minor Q wave myocardial infarction. Troponin T release after transplantation continued for much longer than after myocardial infarction or other cardiac surgery. Processes other than perioperative ischaemic damage must be responsible for the considerable individual differences in the release of cardiac troponin T.